HAK ATAS PELAYANAN KESEHATAN BAGI WARGA BINAAN DI LEMBAGA PEMASYARAKATAN KELAS 1 MEDAN DALAM UPAYA PERLINDUNGAN HAK ASASI MANUSIA - MESARIARO NAZARA; RONY AFRI WARUWU; OBEDI LAIA; AROZATULO MENDROFA (JURNAL ILMIAH KOHESI, 2020)
Correctional Institution is a unit of technical implementation under the Directorate General of Prisons of Kemenkumham (first Department of Justice). Correctional Institution (prison) is a place to undertake the construction of prisoners and correctional students in Indonesia. The fulfillment of human rights is a fundamental right to every human being because it is one of the characteristics of a legal country. However, many conditions in the correctional institution in Indonesia have exceeded the capacity of the defendant who had undergone treatment in prison by changing status to convicted to undergo construction in correctional institution. But many remain in the prison until the time of the criminal is completed. In writing this research using a legal research method is sociological juridical, which is the writing is normative empirical, which is sourced from the center material and the source of the research in the field. As for the problem in this writing is. First, how to implement the fulfillment of health care for the target community in the 1st prison. Secondly, what efforts can be taken to improve the implementation of the fulfillment of health services for the target community in the 1st of the Medan prison. The result of the research that is the implementation of the fulfillment of health care for the target community in the place of Klas 1 Medan is done in two forms that are immediately (uregent) and that are routine. The immediate implementation (urgent) is given to inmates who need handling in heavy-duty or disease-related diseases that require further treatment, where the disease endangers the safety of inmates when not getting immediate treatment (urgent). Efforts that can be traveled to improve the implementation of the fulfilment of health services for the target residents in the prison 1 Medan is composed of a physical examination, Loboratorium, X-rays (as indicated). The implementation of prisoners ' rights and obligations in the form of care, coaching, education and guidance. Health distribution at least 1 (one) time in 1 (one) month and recorded in a health card.